The role of institutional quality in solar energy development: The case of Southeast Asia - Low, Jun Bong; Wong, Ken Fai; Chen, Hou Yao (2024)
This paper investigates the role of institutional quality (IQ) in the development of solar energy in Southeast Asia, using a panel data analysis of 11 countries from 2000 to 2022. Controlling for variables such as GDP, FDI, population, and access to electricity (ATE), the study identifies institutional quality as a key driver of solar energy development. Results indicate that strong institutions—characterized by low corruption, high regulatory quality, and political stability—attract investments in solar infrastructure. GDP and FDI positively influence solar development, while population growth also fosters demand. However, ATE shows a negative impact, as regions with reliable access to conventional electricity may resist adopting solar energy. The findings suggest policy recommendations for Southeast Asian governments to capitalize on population growth by investing in solar energy, offering incentives and subsidies to encourage the transition to sustainable energy